Técnicas de modificación de conducta para disminuir problemas de comportamiento en los niños de 3 a 4 años del centro de desarrollo infantil universitario de la ciudad de Loja, periodo 2018-2019 - Ochoa Calva, Lisbeth Cristina (2020)
This research work entitled: BEHAVIOR MODIFICATION TECHNIQUES TO REDUCE BEHAVIOR PROBLEMS IN CHILDREN FROM 3 TO 4 YEARS AT THE UNIVERSITY CHILDHOOD DEVELOPMENT CENTER IN LOJA CITY, ACADEMIC PERIOD 2018-2019, aims to determine if the Behavior Modification Techniques diminishes behavioral problems in children aged from 3 to 4 years at the university childhood development center in Loja city, academic period 2018-2019. Considering that behavioral problems induce to have difficulties in personal life, family issues or in social interaction in infants, an early intervention is important before the problems become predominant, converting in a problem that needs specialized help. This research work is based on a field design, with a qualitative and quantitative approach; hypothetical, for this investigation the descriptive, analytical-synthetic and inductivedeductive method were applied. Direct observation was the technique employed and an observation sheet was used based on the scales proposed by Isabel Puerta, which was utilized with 12 children. The data showed that the problems sometimes were presented in 39% of pupils, never 35%, frequently 20% and always 7%. According to this, an alternative proposal based on behavior modification techniques was developed with the purpose of reducing those behavioral problems found in kids of the childhood development center, from which positive results were obtained. It was verified that 50% of the population no longer have problems, 42% sometimes and 8% frequently with the application of the post-test. Finally, it can be said that behavior modification techniques are appropriate to reduce or eliminate behavioral problems in younger children, consequently, it is recommended to use the behavior modification techniques in the educational field to improve the problems that makes difficult the teaching-learning process.